Asia's clean revolution : industry, growth and the environment - Angel, David P.; Rock, Michael T. (Greenleaf, 2000)
The world's environmental future will be determined in significant part by what happens in the rapidly industrializing and urban economies of Asia. This work examines the prospects for and pathways to the shaping of a development future that is far less energy-, materials- and waste-intensive.